2010
DOI: 10.1074/jbc.m110.107086
|View full text |Cite
|
Sign up to set email alerts
|

O-Acetylation of Peptidoglycan in Gram-negative Bacteria

Abstract: The ape2 gene encoding a hypothetical O-acetylpeptidoglycan esterase was amplified from genomic DNA of Neisseria gonorrhoeae FA1090 and cloned to encode either the full-length protein or a truncated version lacking its hypothetical signal sequence. Expression trials revealed that production of the fulllength version possessing either an N-terminal or C-terminal His 6 tag was toxic to Escherichia coli transformants and that the host rapidly degraded the small amount of protein that was produced. An N-terminally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…Both domains exhibit sequence identity with PatA (7 and 9% for OatA and OatB, respectively) and PatB (17 and 20%), which were identified, respectively, as the acyl donor transporter and O-acetyltransferase in Neisseria gonorrhoeae (supplemental Fig. S3) (16). Both acetyltransferase domains of OatA and OatB were assigned to the family of SGNH/GDSL hydrolases (LOMETS prediction) as reported for PatB with a conserved Ser-Asp-His predicted catalytic triad ( Fig.…”
Section: O-acetylation Of Murnac and Glcnac Results From Activity Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Both domains exhibit sequence identity with PatA (7 and 9% for OatA and OatB, respectively) and PatB (17 and 20%), which were identified, respectively, as the acyl donor transporter and O-acetyltransferase in Neisseria gonorrhoeae (supplemental Fig. S3) (16). Both acetyltransferase domains of OatA and OatB were assigned to the family of SGNH/GDSL hydrolases (LOMETS prediction) as reported for PatB with a conserved Ser-Asp-His predicted catalytic triad ( Fig.…”
Section: O-acetylation Of Murnac and Glcnac Results From Activity Of mentioning
confidence: 99%
“…However, there is no clear clue to assign any of these conservations regarding to substrate specificity. The globular C-terminal domain, predicted to be surface exposed and assigned to the family of SGNH/GDSL hydrolases, displays a similar conservation level between OatA, OatB, and PatB (32-33% of similarity), the latter being reported to display a MurNAc-specific O-acetyltransferase activity (16). The two most conserved regions GDSV (509 -512 amino acids in OatA Lp ) and DxxH (634 -637 amino acids in OatA Lp ) are supposed to contain the predicted Ser-Asp-His catalytic triad (underlined amino acids) (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, of the many bacteria that have been examined for the presence of O-acetylated PG (6 -8), only E. coli and P. aeruginosa (7) have been found to be devoid of the modification. Thus, we conducted a search of each of the genomes of the Ivy-producing bacteria for the presence of either oatA (18) or the poa cluster (19,20), genes known to encode the enzymes responsible for PG O-acetylation in Gram-positive and Gram-negative bacteria, respectively. Thus, S. aureus OatA (ZP_06334688), N. gonorrhoeae PatB (AAW89271), and B. anthracis Ape3 (NP843402) were used in these BLASTP searches.…”
Section: Identification and Phylogenetic Analysis Of Ivy Homologs Andmentioning
confidence: 99%
“…It was subsequently reported that Ape2 of Neisseria gonorrhoeae does not exhibit esterase activity but functions as a periplasmic protein for the O-acetylation of PG. Thus, the protein was renamed PG O-acetyltransferase B (PatB) (14). PatA and PatB have recently been proposed to function together in translocating acetate from cytoplasmic pools to the periplasm, where it is transferred to peptidoglycan in Gram-negative bacteria (15) (Fig.…”
mentioning
confidence: 99%